LINGUISTIC AND MORPHOLOGIC FEATURES OF ENGLISH AND UZBEK NAMES (Academicia Globe: Inderscience Research, 2021)
The words and phrases which express the place names differs from the other words and phrases which form the dictionary of a language. This feature seems to be connected with the influence of some historical events, several historic persons and natural laws on the appearance of toponomys. Studying and defining these features of such words as toponyms is one of the principal tasks of checking in linguistic aspect.